Water affordability analysis: a critical literature review - Fagundes, Thalita Salgado; Marques, Rui Cunha; Malheiros, Tadeu (Aqua (London, England), 2023)
Water and sanitation affordability has drawn researchers’ attention over the past years due to the recent economic crisis and the growing role of tariffs on funding services. This paper conducted a systematic review of previous research on water and/or sanitation affordability and a critical qualitative discussion on the methodologies adopted. The research framework relied on a hybrid approach that combines systematic quantitative and narrative analyses. The literature review protocol applied returned 79 relevant studies published by journals and recognized international organizations and four key topics, namely affordability indicators, threshold, data source, and practical use of the analysis were identified and critically discussed. This paper contributes to the literature by presenting and discussing the most important water affordability issues and enlightening the potential role of the analysis in public financial policies.